Reliability of isolated hip and shoulder strength measures in female athletes - Cardwell, K.; Kendall, K.; Cochrane Wilke, J.; Nimphius, S. (The Journal of Strength and Conditioning Research, 2021)
Purpose: To assess the test-retest reliability of the ForceFrame in female athletes unfamiliar to isolated joint isometric assessment in the hip and shoulder regions, and examine the inter-method agreement of the ForceFrame and a handheld dynamometer. Methods: Seventeen female state-level softball and baseball athletes were recruited and underwent isometric hip and shoulder strength measures using a ForceFrame and a handheld dynamometer. The movements measured were: hip abduction, hip adduction, hip internal rotation, hip external rotation, shoulder internal rotation, and shoulder external rotation. Testing was conducted 3 times over a 7 day period. Results: Moderate to high reliability was determined for all movements (ICC: 0.59-0.85). Acceptable CVs were found for hip adduction and abduction (4.9-7.9%) and left shoulder external rotation (9.6%); however, the CVs for all other movements were beyond the criterion for reliability (10.6-22.3%). Bland-Altman plots indicate some agreement between the 2 devices, though interchangeable use is not recommended. Conclusions: This study demonstrates that the ForceFrame provides moderate to high reliability in assessing isometric strength of the hips and shoulders in female athletes unaccustomed to isolated joint isometric assessments. Further, these results are similar to the reliability of isometric strength in this population when measured by HHD (ICC: 0.56-0.89). These findings support the use of the ForceFrame for assessing isometric hip and shoulder strength in female athletes in sports where familiarity to isometric testing may be limited. Practical Applications: Field-based isometric testing has previously been restricted to the use of HHD due to its portability and low cost. Yet, previous research has demonstrated shortcomings in the use of HHD. The portability of the ForceFrame allows for easy field-based isometric testing in contrast to laboratory-bound isokinetic dynamometers, while the externally fixed design addresses the reliability issues occasionally found in HHD testing. The reliability of the ForceFrame in measuring isometric shoulder strength provides scientists another valuable instrument for monitoring strength and performance changes throughout the entire kinetic chain.